2018
DOI: 10.1109/tbme.2017.2719400
|View full text |Cite
|
Sign up to set email alerts
|

Limb Position Tolerant Pattern Recognition for Myoelectric Prosthesis Control with Adaptive Sparse Representations From Extreme Learning

Abstract: This method of prosthesis control has the potential to deliver real-world clinical benefits to amputees: better condition-tolerant performance, reduced training burden in terms of frequency and duration, and increased adoption of myoelectric prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 37 publications
1
67
1
Order By: Relevance
“…The first method of minimizing the effect of limb position is the exploration of feature extraction, dimensionality reduction, and classification algorithms that are inherently less susceptible to this effect [23,94,116,130,135,140,[150][151][152]. In an exploratory study conducted by Liu et al [116], repeatability metrics between positions were computed for various commonly used feature sets.…”
Section: Robust Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first method of minimizing the effect of limb position is the exploration of feature extraction, dimensionality reduction, and classification algorithms that are inherently less susceptible to this effect [23,94,116,130,135,140,[150][151][152]. In an exploratory study conducted by Liu et al [116], repeatability metrics between positions were computed for various commonly used feature sets.…”
Section: Robust Algorithmsmentioning
confidence: 99%
“…The application of SRC yielded significantly better performance across all combinations of training and testing positions (p < 0.001). Additionally, the use of extreme learning machines (ELM) in adaptive sparse representation classification (EASRC) greatly reduced computational burden of SRC while maintaining stability under untrained limb positions during an online experiment [150].…”
Section: Robust Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complicating factor of sEMG in the context of natural myocontrol is the limb position effect [6,7,8,9,10,11], namely the change in signals depending on the position and orientation of the limb (body posture). The application of PR by its very nature requires training data that sufficiently captures these variations and it has therefore become bestpractice to perform the acquisition procedure in multiple positions [6,8,12]. Although this strategy seems to be effective in addressing the limb position effect, it comes at the cost of a considerably longer and more tiring acquisition protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the classifiers performance, Adewuyi et al (2016) found for non-amputees and partial-hand amputees that LDA and ANN perform better than the quadratic discriminant analysis. Betthauser et al (2018) developed a robust sparsity-based adaptive classification method to get a classification system which is appreciably less sensitive to signal deviations between training and testing. When they tested it on eight able-bodied and two transradial amputee subjects with eight electrodes pairs regularly spaced around the proximal forearm, it was found that their approach significantly outperformed other movement classification methods.…”
Section: Introductionmentioning
confidence: 99%